CIRC METHOD FOR IMPROVING TEXT ACTIVITIES AND ABILITIES PIWULANGAN SERAT WULANGREH PUPUH GAMBUH - Bambang Cahyono (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
The research aims to find out: (1) the activeness of student learning during the learning process of Serat Wulangreh Pupuh Gambuh using the CIRC method; (2) student learning outcomes in learning the text of Serat Wulangreh Pupuh Gambuh using CIRC method. This type of research is Classroom Action Research (CAR), carried out on students of class VIII of SMP Negeri 2 Ambal Kebumen in 2019/2020 Academic Year. Data collection techniques using: observation, interviews, and assignments. The data validity technique uses source triangulation and method triangulation. Data analysis techniques using interactive and qualitative descriptive model analysis. The results of the study concluded: (1) CIRC learning methods are able to increase student learning activities during the teaching-learning process takes place. This is because students are divided into groups and given assignments in groups. This learning method encourages students to learn to work together that are constructive, respect each other, and avoid egoism that tends to show themselves. In cycle I students who showed high activity were 78% and in cycle II it reached 100%; (2) The CIRC learning method makes it easy for students to understand the contents of the Serat Wulangreh Pupuh Gambuh.